1998
DOI: 10.1055/s-2007-978956
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Long-Term Combined Treatment with Voglibose and Pioglitazone on Pancreatic Islet Function of Genetically Diabetic GK Rats

Abstract: Effects of voglibose (an alpha-glucosidase inhibitor) and pioglitazone (an insulin sensitizer) on glycemic control and on the function of pancreatic islets were evaluated using Goto-Kakizaki (GK) rats with non-insulin-dependent diabetes mellitus (NIDDM). Five week administration (8-13 weeks of age in GK rats) of voglibose alone (added to the chow at a concentration of 10 ppm), pioglitazone alone (10 mg/kg daily p.o.), or both of the agents together significantly improved fasting plasma glucose levels and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…It has been shown that voglibiose the analogue of glucosyl glycerol (GG) may be considered as a therapeutic agent in treatment of diabetes mellitus (Ishida et al 1998 )…”
Section: Production Of Protective Biomoleculesmentioning
confidence: 99%
“…It has been shown that voglibiose the analogue of glucosyl glycerol (GG) may be considered as a therapeutic agent in treatment of diabetes mellitus (Ishida et al 1998 )…”
Section: Production Of Protective Biomoleculesmentioning
confidence: 99%
“…The side effects and safety of acarbose have also been examined [206,207]. Voglibose has been evaluated in NIDDM patients and in combination with pioglitazone in GK rats [208,209]. Miglitol in NIDDM subjects has shown a modest 0.3-0.7% reduction of HbA1c and a slight decrease in serum insulin [210].…”
Section: Glycosidase Inhibitorsmentioning
confidence: 99%
“…Thiazolidinedione derivatives are activators of peroxisome proliferator‐activated receptor‐γ (PPAR‐γ), a member of the nuclear receptor superfamily shown to function in adipogenesis, which results in the an increase of the insulin sensitivity 28 . Treatment of GK rats with voglibose (an α‐glucosidase inhibitor) and with voglibose plus pioglitazone (a thiazolidinedione derivative) for 5 weeks significantly increased 16.7 mmol/L glucose‐induced insulin secretion compared with control GK rats 29 …”
Section: Discussionmentioning
confidence: 99%